Color parameters applied to pedotransfer functions in the estimation of soil attributes - De Lima Cruz, Nara Núbia; Barbosa, Ronny Sobreira; De Moura, Marcio Cleto Soares; De Bortoli Teixeira, Daniel; Júnior, José Marques [UNESP]; De Deus Ferreira E Silva, João (My University, 2018)
Global demands for an increased food production have prompted scientists to create technological innovations in various segments of the agricultural and environmental sectors. The use of diffuse reflectance spectroscopy in soil color determination to estimate its attributes is an example of these advances. Thus, the aim of this research was to identify the potential of the three parameters of the Munsell color system (Hue, Value, and Chroma) in estimating different chemical and particle size attributes by pedotransfer functions in a Typic Hapludox in the Cerrado of Piauí State, Brazil. This soil showed a yellowish color due to the goethite and low contents of bases and organic carbon. Among the calibrated pedotransfer functions, we observed that phosphorus, aluminum, hydrogen, potential acidity, potential cation exchange capacity, and base saturation could be estimated by Hue, while clay content by Value, and Chroma used to estimate hydrogen, potential acidity, and cation exchange capacity. We conclude that the parameter color could be used to estimate soil attributes.
Keywords: Cerrado of Piauí State; Diffuse reflectance spectroscopy; Linear regression; Munsell color system; Sandy-loam soil; Typic Hapludox